Developing land-based infrastructure to mitigate the challenges of soil productivity per unit land - S, Rakesh; B, Dastagiri M; Juttu, Ravinder; Jogula, Kamalakar; Raju, Bairi; Reddy, Sharan Bhoopal (Indian Farming, 2021)
Since beginning until 1950 or so, global food production growth resulted entirely from expanding the cultivation area. The world began systematically to raise land productivity as the frontiers of agricultural settlement disappeared. Looking back, the greatest progress in eradicating hunger, a tremendous pressure on farming lands consequently resulted into poor soils with low productivity besides degrading the natural ecosystem. Present article focusses on the key causes and impacts of poor soil productivity in farming and the technological promotion and action plan for achieving development of land-based infrastructure.